Postoperative C-Reactive Protein as a Biomarker for Complications Following Gastrectomy in Gastric Cancer Patients - Ter, Yen Bi; Thi, Wor Mi; Htike, Kyaw Min; U, Ei Sandar (Journal of Health Science and Alternative Medicine, 2024)
Introduction: Globally, gastric cancer ranks as the fifth most prevalent malignancy and the third leading cause of mortality related to cancer, with surgical resection being merely a curative treatment option. Postoperative complications continue to pose major challenges that impact patient outcomes and require prompt detection and management. C-reactive protein (CRP) had the potential role in predicting postoperative complications, but the knowledge was limited in different healthcare settings. The study aimed to identify the predictive role of CRP levels tested on postoperative day 4 (POD4) on the occurrence of complications in gastric cancer patients following gastrectomy. Methods: This was a single-center, cross-sectional study conducted in two hospitals in Myanmar. The study included 145 patients scheduled for gastrectomy. Data collection involved patient records, clinical examinations, and laboratory investigations. The association between CRP and post gastrectomy complication was analyzed by independent t-test and multiple logistic regression. The association was described using an Adjusted Odds Ratio (AOR), 95% Confidence Interval (CI), and p-value. The statistically significant level was considered at the p-value of < 0.05. Results: The mean age of patients was 59.5 years, with a predominance of males (58.6%). Complications were identified in 12.4% of cases (95%CI=7.52-18.91). The mean CRP level for patients without complications was 107.98 mg/L, compared to 178.99 mg/L for those with complications (p-value<0.001). Specifically, patients with anastomotic leaks had a mean CRP level of 254 mg/L. Multiple logistic regression analysis indicated that elevated POD4 CRP levels were a significant predictor of complications, with an AOR of 1.38 (95%CI=1.12-1.71). The cut-off CRP value of 135.8mg/L demonstrated the best predictable level for complications with an Area Under ROC curve of 86.0%, a sensitivity of 72.2%, and a specificity of 99.2%. Conclusion: This study highlighted CRP as a biomarker for complications in gastric cancer patients undergoing gastrectomy. Elevated CRP levels may assist clinicians in identifying at-risk patients, thereby enabling timely interventions and improved patient outcomes.